Vascular damage and EEG markers in subjects with mild cognitive impairment - Moretti, D.V.; Miniussi, C.; Frisoni, G.; Zanetti, O.; Binetti, G.; Geroldi, C.; Galluzzi, S.; Rossini, P.M. (Clinical neurophysiology, 2007)
We evaluated the changes induced by cerebrovascular (CV) damage on brain rhythmicity recorded by electroencephalography (EEG) in a cohort of subjects with mild cognitive impairment (MCI). We enrolled 99 MCI subjects (Mini-Mental State Examination [MMSE] mean score 26.6). All subjects underwent EEG recording and magnetic resonance imaging (MRI). EEGs were recorded at rest. Individual EEG frequencies were indexed by the θ/ α transition frequency (TF) and by the individual α frequency (IAF) with power peak in the extended α range (5–14 Hz). Relative power was separately computed for δ, θ, α1, α2, and α3 frequency bands on the basis of the TF and IAF values. Subsequently, we divided the cohort in four sub-groups based on subcortical CV damage as scored by the age-related white matter changes scale (ARWMC). CV damage was associated with ‘slowing’ of TF proportional to its severity. In the spectral bandpower the severity of vascular damage was associated with increased δ power and decreased α2 power. No association of vascular damage was observed with IAF and α3 power. Moreover, the θ/ α1 ratio could be a reliable index for the estimation of the individual extent of CV damage. EEG analysis may show physiological markers sensitive to CV damage. The appropriate use of this EEG index may help the differential diagnosis of different forms of cognitive decline, namely primary degenerative and secondary to CV damage. The EEG neurophysiological approach, together with anatomical features from imaging, could be helpful in the understanding of the functional substrate of dementing disorders.